Modelling perceived e-learning service quality, student satisfaction and loyalty. A higher education perspective - Phillip Dangaiso; Forbes Makudza; Hope Hogo (Taylor and Francis Group, 2022)
Blended e-learning has become a common phenomenon in higher education globally. Most affluent economies embraced e-learning by design through strategic moves to augment their competitiveness. However, in most emerging economies, e-learning implementation was impulsively reactive to the Covid-19ʹs demands. Thus, the study examined the impact of perceived e-learning service quality on students’ satisfaction and loyalty in a developing country. The expectation-confirmation thty -35 eory informs the development of the conceptual framework. A causal research design enshrined in the positivism research philosophy was adopted. The research population was made up of students enrolled in public and private universities in Zimbabwe. Data was collected through person-administered survey and a stratified sample of 354 students was obtained. The results from structural equation modelling (SEM) revealed significant positive relationships between perceived e-learning service quality dimensions and e-learning student satisfaction. It was also reflected that student satisfaction positively affected student loyalty with e-learning (P < 0.05). It was therefore concluded that system quality, information quality and service quality significantly influence student satisfaction and loyalty with e-learning. The study thus recommended that the higher education industry should design e-learning systems that enhance easy access, easy navigation and user flexibility.